IDNLearn.com offers a comprehensive platform for finding and sharing knowledge. Our experts provide accurate and detailed responses to help you navigate any topic or issue with confidence.
Sagot :
To solve for [tex]\( c \)[/tex] in the equation [tex]\( 5c - 2 = 3c \)[/tex], let's go through the steps to isolate [tex]\( c \)[/tex].
1. Subtract [tex]\( 3c \)[/tex] from both sides of the equation:
[tex]\[ 5c - 3c - 2 = 3c - 3c \][/tex]
Simplify to:
[tex]\[ 2c - 2 = 0 \][/tex]
2. Add 2 to both sides of the equation to further isolate the term with [tex]\( c \)[/tex]:
[tex]\[ 2c - 2 + 2 = 0 + 2 \][/tex]
Simplify to:
[tex]\[ 2c = 2 \][/tex]
3. Divide both sides by 2 to solve for [tex]\( c \)[/tex]:
[tex]\[ \frac{2c}{2} = \frac{2}{2} \][/tex]
Simplify to:
[tex]\[ c = 1 \][/tex]
Now, we need to find [tex]\( 24c \)[/tex].
4. Multiply [tex]\( c \)[/tex] by 24:
[tex]\[ 24c = 24 \times 1 \][/tex]
[tex]\[ 24c = 24 \][/tex]
Therefore, [tex]\( 24c = 24 \)[/tex].
So, the correct answer is:
[tex]\[ 24 \][/tex]
1. Subtract [tex]\( 3c \)[/tex] from both sides of the equation:
[tex]\[ 5c - 3c - 2 = 3c - 3c \][/tex]
Simplify to:
[tex]\[ 2c - 2 = 0 \][/tex]
2. Add 2 to both sides of the equation to further isolate the term with [tex]\( c \)[/tex]:
[tex]\[ 2c - 2 + 2 = 0 + 2 \][/tex]
Simplify to:
[tex]\[ 2c = 2 \][/tex]
3. Divide both sides by 2 to solve for [tex]\( c \)[/tex]:
[tex]\[ \frac{2c}{2} = \frac{2}{2} \][/tex]
Simplify to:
[tex]\[ c = 1 \][/tex]
Now, we need to find [tex]\( 24c \)[/tex].
4. Multiply [tex]\( c \)[/tex] by 24:
[tex]\[ 24c = 24 \times 1 \][/tex]
[tex]\[ 24c = 24 \][/tex]
Therefore, [tex]\( 24c = 24 \)[/tex].
So, the correct answer is:
[tex]\[ 24 \][/tex]
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Thank you for choosing IDNLearn.com for your queries. We’re committed to providing accurate answers, so visit us again soon.